Acacia Species as Browse forGoats in Arid and Semi-Arid Regions in Kenya - H. C, Kandie; J. K , Kitilit; G, W. O. , Oliech; J. O , Ondiek (African Journal of Education,Science and Technology (AJEST), 2024)
The study evaluated the preference of specific Acacia spp, by goats in Chemeron, Baringo County, Kenya using natural browsing method. Pastoralism in arid and semi-arid lands(ASALs), face significant constraints due to insufficient and inadequate nutritious feeds. However, the region holds several fodder trees and shrubs which are important feed sources. The study area is part of the ASAL where the major browse plants including Acacia species are situated. The study used natural browsing method as a form of randomized experimental design in a natural setting where goats are left unconstrained to browse on any type of shrub or tree and in particular their preferred Acacia spp. This design was preferred because of the randomness of the choice of the Acacia trees species, the flexibility of choice of replicates and treatments and lastly, the method allows for natural preference within the contextual setting. Browsing data was obtained ophthalmologically after every 5 minutes for a period of 160 minutes. Once the data, had been transcribed and processes, preference statistic was estimated through Kruskal-Wallis test, (χ2 (4) = 182.6, p< 0.05) which indicated statistically significant differences in browsing preferences among the Acacia spps. The findings showed that certain Acacia spp. were highly preferred over other species by goats with A. brevispica, A. tortilis and A. nilotica being ranked highly while A. senegal having the lowest rank. In conclusion the most preffered browse species in ASAL include A. brevispica, A. nilotica and A. Tortilis, while acacia Senegal is the least preferred by the indeginous goats. The preferred species may be considered as supplements or as alternative livestock feeds depending on the agro-climatology and topography of the region. Therefore, there is need to propagate certain Acacia spps which include A. brevispica, A. nilotica and A. tortilis as alternative fodder crops of ASAL. These browses can be grown as fodder banks, live fences, alleys or silvopastoral systems and managed to provide fodder on a continuous basis or for harvest and processing for use in droughts as good source of nutrients for use in livestock production in ASAL regions. Lastly, the study focused on the identification of preferred Acacia spp. in a particular region in Kenya, whereas other studies may focus on development of a database containing favourable fodder tree crops.